Bullet proof [videorecording (DVD)] - Peever, Ben (Lionsgate, 2022)
After stealing millions in cash from Temples's drug-dealing hideout, a thief finds a stowaway in his getaway car, who turns out to be Temple's pregnant wife Mia! Desperate to reclaim his cash and his unborn son, Temple sends out a squad of hit men and bounty hunters to bring in Mia and the thief. Speed, cleverness, and good aim give the duo a brief advantage, but how long will their luck hold out?